Exploring confocal laser scanning microscopy (CLSM) and fluorescence staining as a tool for imaging and quantifying traces of marine microbioerosion and their trace‐making microendoliths. (27th July 2021) - Schätzle, Philipp‐Konrad; Wisshak, Max; Bick, Andreas; Freiwald, André; Kieneke, Alexander
Abstract: Microscopic organisms that penetrate calcareous structures by actively dissolving the carbonate matrix, namely microendoliths, have an important influence on the breakdown of marine carbonates. The study of these microorganisms and the bioerosion traces they produce is crucial for understanding the impact of their bioeroding activity on the carbonate recycling in environments under global climate change. Traditionally, either the extracted microendoliths were studied by conventional microscopy or their traces were investigated using scanning electron microscopy (SEM) of epoxy resin casts. A visualisation of the microendoliths in situ, that is within their complex microbioerosion structures, was previously limited to the laborious and time‐consuming double‐inclusion cast‐embedding technique. Here, we assess the applicability of various fluorescence staining methods in combination with confocal laser scanning microscopy (CLSM) for the study of fungal microendoliths in situ in partly translucent mollusc shells. Among the tested methods, specific staining with dyes against the DNA (nuclei) of the trace making organisms turned out to be a useful and reproducible approach. Bright and clearly delineated fluorescence signals of microendolithic nuclei allow, for instance, a differentiation between abandoned and still populated microborings. Furthermore, infiltrating the microborings with fluorescently stained resin seems to be of great capability for the visualisation and quantification of microbioerosion structures in their original spatial orientation. Potential fields of application are rapid assessments of endolithic bio‐ and ichnodiversity and the quantification of the impact of microendoliths on the overall calcium carbonate turnover. The method can be applied after CLSM of the stained microendoliths and retains the opportunity for a subsequent investigation of epoxy casts with SEM. This allows a three‐fold approach in studying microendoliths in the context of their microborings, thereby fostering the integration of biological and ichnological aspects of microbial bioerosion. Lay Description: Bioerosion describes the process of active erosion of hard substrates induced by the activity of living organisms. Beside numerous marine macroscopic bioeroding organisms such as sponges, annelids or bivalves, there is an astonishing 'hidden diversity' of microscopic bioeroding organisms which produce minute tunnels and chambers, for example in calcareous shells and skeletons of other marine organisms. These so‐called microendoliths belong to bacteria, microalgae, foraminiferans, or fungi. Due to their lifestyle hidden inside the hard substrate, scientific investigation is often laborious and involves complex preparation techniques, electron microscopy, or even nano‐computed tomography. Photo‐autotrophic microendoliths (eg cyanobacteria and algae) have been studied with fluorescence microscopy using autofluorescence properties, for example of their chloroplasts. However, microendoliths of aphotic depths, mostly of fungal origin, do not show autofluorescence. With the present study we test different fluorescent dyes staining the microbioeroders ' in situ', that is, inside their microscopic tunnels, and visualise them using three‐dimensional confocal laser scanning microscopy (CLSM). Very good results have been obtained with the dye Sybr Green I that stains DNA molecules and thereby the cell nuclei of the microendoliths. This method can be used, for instance, to measure the infestation rate of a given substrate by discriminating between abandoned microborings and those still inhabited by microendoliths. Another approach that was successfully tested in the course of the present study was the infiltration of the cleaned microborings with resin that was previously mixed with the fluorescent dye Safranin‐O. The datasets obtained with the CLSM were used to reconstruct 3D‐surface models of the microborings of three different microendoliths. Such models can be used to analyse the original spatial arrangement inside the hard substrate and to measure exact volumes. The resulting possibility to make exact quantifications is of high value for future investigations that focus on the role and proportion of microbioerosion in the (re)cycling of marine carbonates.